AEO Programmes Worldwide: From MRAs to a General AEO Agreement?! - Carsten Weerth (Global Trade and Customs Journal, 2015)
The Authorized Economic Operator (AEO) status is being introduced around the globe in more and more countries in order to combat terrorism by better security measures in World Trade. This paper gives an overview about existing AEO programmes and new AEO programmes which are about to start in 2015. It describes in detail the Mutual Recognition Agreements (MRAs) which have been concluded to date. And it calls for a General AEO Agreement in order to facilitate the AEO acknowledgement by traders and governments alike in many less developed countries of the world.
Additional information: Pre-Print-Proofs according to the Romeo/Sherpa policy of this yellow Journal.
Keywords: F53; K33; K34; 330; Customs Law; World Customs Organization; Authorized Economic Operator; Supply chain risk management; Trade Facilitation; Trade policy